Basing Intranet Design on the Organizational Information Environment and User Information Behaviour - Detlor, Brian (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper explores the viability of a new approach to intranet design, on that is based on an understanding of the organizational information environment and user information behaviour. The approach was used by 11 project teams of graduate students to develop intranet designs for local organizations. The workbooks used by the project teams were analysed to identify the components. .